EFFECT OF HEPARIN, ESTROGEN ON EPIDIDYMAL SPERM CAPACITATION AND IN VITRO FERTILIZATION IN IRAQI SHEEP - & Saleh, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was designed to study the capacitation of caudal spermatozoa in vitro by different levels of heparin, estrogen for in vitro fertilization (IVF) in the Iraqi local sheep. Results of sperm capcitation (massive motility percentage) by applying three levels of heparin (50, 100, 150) IU in relation to breeding season showed no significant differences during breeding season with the three levels, which were (82.23 ± 0.58), While results by applying the higher level of heparin (150) IU out of breeding season showed significantly (P